Viscovery: Trend Tracking in Opinion Forums based on Dynamic Topic Models- - Ignacio Espinoza; Marcelo Mendoza; Pablo Ortega; Daniel Rivera; Fernanda Weiss (Journal of Digital Information Management, 2019)
Opinions in forums and social networks are released by millions of people due to the increasing number of users that use Web 2.0 platforms to opine about brands and organizations. For enterprises or government agencies it is almost impossible to track what people say producing a gap between user needs/ expectations and organizations actions.